THE DEVELOPMENT OF MATHEMATICAL MODEL AND THEORETICAL ANALYSIS OF THE ROLLING PROCESS IN HIGH-SPEED REDUCING-CALIBRATION BLOCK OF MODERN WIRE MILL - S. M. Zhuchkov; A. A. Gorbanev; V. A. Matochkin (Литьë и металлургия)
Тhе mathematical model of the process of continuous rolling in reducing-calibrating block, with the help of which the theoretical analysis of this process is carried out, is developed.